Artificial intelligence based on agent based modelling with cyber security for remote operated vehicle on dangerous terrain - Kumari, Priyanka; T. Aarthy, S (International Journal of Engineering and Technology, 2018)
A major problem of decision making for autonomous robots is the localization of the robots towards the origin. The point on which the paper is mainly focusing to save human lives, money and conserve the environment too. In the proposed project a firefighter robot is implemented which is efficient to detect fire flame and smoke and cyber security are implemented to secure the data that are recorded in a web page. Here using the RGB to HSV algorithm and motion detection algorithm to detect the fire flame and smoke in python language.